Sistema multidimensional y cuadro de mando integral con fuentes de información del sistema materno neonatal del Ministerio de Salud Pública - Enríquez Chamba, Lidia Esperanza (2023)
In the Zonal Coordination 3 of the Ministry of Public Health, large amounts of data need to be analyzed. Currently, there are reports from 278 facilities in a District Report Matrix of Maternal Neonatal Care Monitoring, depriving them of obtaining helpful information that would allow them to make organizational decisions and provide quality care. Regarding this need, this research focuses on the design of a multidimensional system and an Integral Dashboard. The research was developed under the Crisp-DM methodology. Through six phases, helped obtain quality data with criteria: complete, credible, and accurate as established by ISO/IEC 25012 standard, through the Talend Data Quality tool. Free tools such as Pentaho were used to perform ETL processes, R Studio for programming the Integral Dashboard, and the Shiny library as a server to visualize the Integral Dashboard. The data analysis process considered six tables: Province, Canton, Zone, Indicator, Facts, Time, and Establishment. Results of 100% completeness, 100% credibility, and 100% accuracy of the data were obtained in each table. The results are high-quality data according to the metrics provided by the ISO/IEC 25012 standard. The final result of the thesis is a multidimensional system and an Integral Dashboard that allows users to access essential and valuable information about the Maternal Neonatal System of the Ministry of Public Health.